2019
DOI: 10.1186/s40851-019-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

X-ray imaging of a water bear offers a new look at tardigrade internal anatomy

Abstract: Background Tardigrades (water bears) are microscopic invertebrates of which the anatomy has been well studied using traditional techniques, but a comprehensive three-dimensional reconstruction has never been performed. In order to close this gap, we employed X-ray computed tomography (CT), a technique that is becoming increasingly popular in zoology for producing high-resolution, three-dimensional (3D) scans of whole specimens. While CT has long been used to scan larger samples, its use in some mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Detailed comparison of our findings with those from the other two extant panarthropod groups, the arthropods and tardigrades, is also problematic. The marine and limnoterrestrial tardigrades are the only other extant panarthropod group that shows unjointed limbs [21,22]. However, miniaturization in these animals seems to have led to a reduction in the individual muscles to single myocytes [21,51].…”
Section: Resultsmentioning
confidence: 99%
“…Detailed comparison of our findings with those from the other two extant panarthropod groups, the arthropods and tardigrades, is also problematic. The marine and limnoterrestrial tardigrades are the only other extant panarthropod group that shows unjointed limbs [21,22]. However, miniaturization in these animals seems to have led to a reduction in the individual muscles to single myocytes [21,51].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, microCT has been integrated increasingly in correlative microscopy applications, to define VOIs and as a reference for sectioning-based microscopy 4,13,31 . But to genuinely gain information about the microstructure of tiny biological specimens, the resolution of conventional microCT does not suffice 8 .…”
Section: Discussionmentioning
confidence: 99%
“…CLEM is a collective term for all different combinations of light and electron microscopy, ranging from fluorescence super-resolution microscopy to conventional bright field light microscopy and from focused-ion-beam scanning electron microscopy (FIB-SEM) over serial-block-face SEM (SBF-SEM) to transmission electron microscopy (TEM) 1,4-6 . Since light and electron microscopy techniques conventionally feature limited penetration depths through matter, they typically rely on sectioning or complete destruction of the sample to create 3D information of entire small biological specimens 1,7,8 . This often prevents isotropic resolution, and the resulting data are affected by deficiencies such as sectioning and alignment artefacts 1,4,5 .X-ray computed tomography (CT) is a widely used tool for non-destructive 3D imaging with isotropic resolution 3,9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although searching on the mechanisms has revealed their differentiation between tardigrade species (e.g. Hengherr et al, 2008; Rebecchi et al, 2013; Bemm et al, 2017; Gross et al, 2019; Kamilari et al, 2019), available data appears to indicate common and important role of proper mitochondria functioning. Accordingly, it has been shown that mitochondria uncoupling abolishes tun formation (Halberg et al, 2013) and reactive oxygen species (ROS) generated in majority by mitochondria (e.g.…”
Section: Introductionmentioning
confidence: 99%